Quartet Card Games to Improve Knowledge, Behavior and Attitude of Children About Dental and Oral Health - Laila, Nur; Tulloh, Rizki Rachmat; Iswati, Ning (Jurusan Keperawatan FIKES UNSOED, 2018)
Dental caries is a common problem in children. Health education by playing games is necessary to improve skills of children in dental care and oral health. Health education materials with quartet cards are presented in the form of pictures and interesting information. The purpose of this study was to determine the effect of quartet card game method in improving knowledge and attitude about oral and dental health. The study used quasi experiment research with pre and post-test group designs. Samples were 56 children aged 8-10 years. Data analysis used paired sample-test. The results show that there was an increase in knowledge and attitude after health education using a quartet card game. Regarding knowledge, analysis showed t=13.635, p value = 0.000, Î±: 0.05, while on attitude aspect, analysis showed t= 9,352 and p-value = 0.000 Î±: 0.05. Quartet card game is effective to improve knowledge and attitude about dental care and oral health among children.